Design of single phase inverter for photovoltaic application controlled with sinusoidal pulse width modulation - Ibrahim Alhamrouni; N. Zainuddin; Mohamed Salem; Nadia H. A. Rahman; Lili Awalin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The application of fossil fuels likes coal, oil and gas gives the enormous environmental impact and hazardous effects to the earth. Hence, renewable energy has become the most tremendously friendly methods to generate the electricity without pollution and emissions. Inverter is a power electronics device which is used to convert Direct Current (DC) into Alternating Current (AC). The conventional inverter no longer fulfills the requirement of reducing harmonic distortions plus it causes global warming and greenhouse effect. For increasing the efficiency and reliability of the system, the PV inverter becomes a vital part in the conversion of DC to AC output. This research thus presents a single phase photovoltaic inverter controlled with sinusoidal pulse-width-modulation (SPWM) and low pass filter connection between the inverter and the utility grid to reduce the harmonics due to intermittent nature of the renewable energy sources. Unipolar and Bipolar switching scheme are applied to control the magnitude and frequency of output voltage and result of both unipolar and bipolar are compared. The simulation of the proposed technique is executed by using Matlab/Simulink.